BRIDGING GLOBAL MINDSET AND LOCAL ACTION: CROSS-CULTURAL CHALLENGES IN CULTIVATING ENTREPRENEURIAL COMPETENCE AMONG UNIVERSITY STUDENTS (Web of Teachers: Inderscience Research, 2025)
In the context of accelerating globalization, higher education institutions face growing pressure to prepare students not only for local labor markets, but also for global entrepreneurial ecosystems. However, the formation of entrepreneurial competence is significantly influenced by cultural values, national educational traditions, and socio-economic contexts. This article explores the cross-cultural challenges inherent in cultivating entrepreneurial culture among university students from diverse backgrounds. The article concludes with implications for curriculum design, educator training, and policy reform, emphasizing the need for adaptive, culturally nuanced strategies in entrepreneurial education.